2017
DOI: 10.1016/j.cub.2017.03.059
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Evolution of the Cerebellum in Humans and Other Great Apes

Abstract: . (2014) 'Rapid evolution of the cerebellum in humans and other great apes. ', Current biology., 24 (20). pp. 2440-2444. Further information on publisher's website:http://dx.doi.org/10. 1016/j.cub.2014.08.056 Publisher's copyright statement: NOTICE: this is the author's version of a work that was accepted for publication in Current Biology. Changes resulting from the publishing process, such as peer review, editing, corrections, structural formatting, and other quality control mechanisms may not be ree… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
66
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(77 citation statements)
references
References 23 publications
11
66
0
Order By: Relevance
“…Across primates, variation in cerebellum volume is linked to extractive foraging, after controlling for variation in neocortex volume [Barton, 2012]. The importance of the cerebellum in primate brain evolution is further bolstered by comparative analyses that demonstrate the cerebellum is expanded in hominoids [Rilling and Insel, 1998;MacLeod et al, 2003] due to a non-allometric expansion of the cerebellum relative to neocortex size that was caused by a faster-than-expected increase in cerebellum volume and neuron number that persisted throughout hominoid evolution [Barton and Venditti, 2014]. Although data at increasingly fine grained levels are more limited, the volumetric expansion of the whole cerebellum appears to be driven by a specific increase in the cerebellar lateral hemispheres [MacLeod et al, 2003] and possibly specific areas which receive direct functional connections with the prefrontal cortex [Balsters et al, 2010], an area of the neocortex long thought to be selectively expanded in hominoids [e.g., Semendeferi et al, 2001;Schoenemann et al, 2005;Sherwood et al, 2005;Smaers et al, 2011, but see Barton and Venditti, 2013;Gabi et al, 2016].…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…Across primates, variation in cerebellum volume is linked to extractive foraging, after controlling for variation in neocortex volume [Barton, 2012]. The importance of the cerebellum in primate brain evolution is further bolstered by comparative analyses that demonstrate the cerebellum is expanded in hominoids [Rilling and Insel, 1998;MacLeod et al, 2003] due to a non-allometric expansion of the cerebellum relative to neocortex size that was caused by a faster-than-expected increase in cerebellum volume and neuron number that persisted throughout hominoid evolution [Barton and Venditti, 2014]. Although data at increasingly fine grained levels are more limited, the volumetric expansion of the whole cerebellum appears to be driven by a specific increase in the cerebellar lateral hemispheres [MacLeod et al, 2003] and possibly specific areas which receive direct functional connections with the prefrontal cortex [Balsters et al, 2010], an area of the neocortex long thought to be selectively expanded in hominoids [e.g., Semendeferi et al, 2001;Schoenemann et al, 2005;Sherwood et al, 2005;Smaers et al, 2011, but see Barton and Venditti, 2013;Gabi et al, 2016].…”
Section: Introductionmentioning
confidence: 96%
“…1 d). Again, given available GO data, these contrasting proportions suggest that the strength of positive selection acting on genes controlling cerebellum development may have increased during hominoid evolution, a clade in which the rate of cerebellar expansion significantly accelerated [Barton and Venditti, 2014] beyond the rate predicted based on scaling with the neocortex in other primates [Barton and Harvey, 2000;Barton and Venditti, 2013].…”
Section: Do Rates Of Molecular Evolution Reflect Rates Of Brain Compomentioning
confidence: 99%
“…For example, the neocortex has generally increased in size disproportionally compared to the other structures in primates, betraying selection on this structure. At the cellular level, the ratio of number of neurons in the cerebellum and neocortex remains almost constant (Herculano-Houzel 2010 see also Barton and Venditti 2014). This does not mean that the selection for these two structures has been of similar importance (since they have different patterns of connectivity), nor that these two structures have a comparable influence in the brain network.…”
Section: B3 Relative Structure Sizementioning
confidence: 87%
“…This study was done in 12 adult human brains, regardless their sex. Other study showed that there are approximately 70 billion of neurons can be observed in the adult human cerebellum, with most of them reside at the granular layers (Barton & Venditti, 2014). These cells formed the cerebellar folia, which are vast in numbers depend on the learned sequential movement in one's daily life.…”
Section: Discussionmentioning
confidence: 99%